Listening to the student voice on emergency remote teaching during the pandemic crisis - Y D Kristanto; B Utomo; N Sulistyani (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2021)
There is a need to evaluate emergency remote teaching (ERT) effort during COVID-19 pandemic to design and plan more effective online distance learning. Students’ voices are valuable input in evaluating ERT practice since the students are the ones most directly affected. This study aims to describe the students’ voice regarding their experiences and expectations while being enrolled in ERT-based courses in a time of COVID-19 pandemic. This study used mixed methods with survey approach in describing the students’ voice. Quantitative data analysis shows that the Community of Inquiry (CoI) elements, technology use, internet quality, and student perceived satisfaction are related to each other. As from the qualitative data analysis, seven main themes are obtained from students’ responses, namely instructor’s orchestration, assignments and internet constraints, learning process, the flexibility of emergency remote teaching, interaction among course participants, experiences in synchronous learning, as well as self- and co-regulation. The results in this study are expected to provide insightful input for the online instructor, learning designer, and policymaker in designing and planning more effective online distance learning programs